JUXTA-ARTICULAR MYXOMA OF THE SHOULDER IN AN 85-YEAR-OLD FEMALE: A CASE REPORT AND LITERATURE REVIEW. (February 2015) - Popp, Benjamin; Chan, Stephen
Abstract : Juxta-articular myxoma is rare soft tissue tumour of uncertain differentiation, which commonly arises in close proximity to large joints, in particular the knee.1 This case review involves an 85-year-old woman who presented with an intermittently painful, slowly growing mass overlying the right deltoid. The mass enlarged over a period of years following a fall onto her right arm and was more rapidly growing in recent months. CT imaging demonstrated a well-circumscribed mass overlying the right deltoid with the superior aspect in close proximity to the right shoulder bursa. Macroscopically the tumour (85 × 40 × 40 mm) cut surface was slimy and gelatinous with occasional clear viscous fluid filled cysts ranging from 2–20 mm. Microscopically the lesion was hypocellular and composed of bland spindle cells in a myxoid stroma with occasional cystic, ganglion-like spaces with various wall linings ranging from fibrin through to a thick layer of collagen. The tumour cells were shown to be CD34, SMA and vimentin positive as well as S100 negative. Whilst the identification of a myxoma is not challenging, identification of a juxta-articular myxoma requires careful consideration of the clinical, radiological and pathological details, which will be presented in full along with a review of the literature.